SIRT5 inhibits peroxisomal ACOX1 to prevent oxidative damage and is downregulated in liver cancer - Chen, Xiu‐Fei; Tian, Meng‐Xin; Sun, Ren‐Qiang; Zhang, Meng‐Li; Zhou, Li‐Sha; Jin, Lei; Chen, Lei‐Lei; Zhou, Wen‐Jie; Duan, Kun‐Long; Chen, Yu‐Jia; Gao, Chao; Cheng, Zhou‐Li; et al. (EMBO reports, 2018)
Peroxisomes account for ~35% of total H 2 O 2 generation in mammalian tissues. Peroxisomal ACOX1 (acyl‐CoA oxidase 1) is the first and rate‐limiting enzyme in fatty acid β‐oxidation and a major producer of H 2 O 2 . ACOX1 dysfunction is linked to peroxisomal disorders and hepatocarcinogenesis. Here, we show that the deacetylase sirtuin 5 (SIRT5) is present in peroxisomes and that ACOX1 is a physiological substrate of SIRT5. Mechanistically, SIRT5‐mediated desuccinylation inhibits ACOX1 activity by suppressing its active dimer formation in both cultured cells and mouse livers. Deletion of SIRT5 increases H 2 O 2 production and oxidative DNA damage, which can be alleviated by ACOX1 knockdown. We show that SIRT5 downregulation is associated with increased succinylation and activity of ACOX1 and oxidative DNA damage response in hepatocellular carcinoma (HCC). Our study reveals a novel role of SIRT5 in inhibiting peroxisome‐induced oxidative stress, in liver protection, and in suppressing HCC development. Synopsis This study reveals a role for SIRT5 in regulating peroxisomal H 2 O 2 and ROS homeostasis and indicates its potential function in liver protection and hepatocellular carcinoma suppression. SIRT5 is localized in peroxisomes where it controls H 2 O 2 metabolism. SIRT5‐mediated desuccinylation inhibits ACOX1 activity by suppressing its active dimer formation. SIRT5 downregulation increases ACOX1 activity and oxidative DNA damage response in HCC. Graphical Abstract This study reveals a role for SIRT5 in regulating peroxisomal H 2 O 2 and ROS homeostasis and indicates its potential function in liver protection and hepatocellular carcinoma suppression.